Curative effect of different drainage methods on laparoscopic inguinal hernia repair: A meta-analysis. Issue 34 (26th August 2022) - Zhong, Yang; Liu, Zhi; He, Miao; Lv, Xiao Jiang; Liu, Mao; Wen, Ai Ping; Chen, Jian Yu; Qin, Long; Li, Jian Shui
Abstract : Background: Laparoscopic inguinal hernia repair has developed rapidly as an important surgical method for inguinal hernia repair; however, postoperative complications, especially postoperative seroma, are becoming an important factor hindering its development. Many studies have shown that placing a negative-pressure drainage tube in the preperitoneal space can effectively reduce postoperative seromas. Accordingly, this study aimed to compare differences in postoperative seroma between surgical procedures with drainage tubes (DRG) and those without drainage tubes (nonDRG). Methods: PubMed/Medline, EMBASE, Cochrane Library, China National Knowledge Infrastructure, and Wanfang databases were searched from the establishment of the database to May 1, 2021. Odds ratio (OR), mean difference (MD), standardized mean difference (SMD), and 95% confidence interval (CI) were selected as the effect scale indices for the evaluation of the difference in seroma, operation time, hospital stay time, blood loss, and recovery time. All of these were compared using RevMan 5.3 Software. Results: Sixteen studies involving 4369 patients, 2856 in the DRG group and 1513 in the nonDRG group, were included. The incidence of seroma in the DRG group was lower than that in the nonDRG group (OR = 0.16, 95% CI: 0.07–0.35, P < .001). Additionally, the operation time (min) in the DRG group was longer than that in the nonDRG group (MD = 3.67, 95% CI: 2.18–5.17, P < .001). Nevertheless, no significant differences were found in hospital stay (days) (SMD = 0.22, 95% CI: −0.10–0.54, P = .17), blood loss (mL) (MD = 0.28, 95% CI: −0.14–0.69, P = .19), and recovery time (h) (SMD = 0.54, 95% CI: −0.60–1.69, P = .35) between the 2 groups. Conclusion: Despite the slightly prolonged operation time, negative pressure drainage in the preperitoneal space during laparoscopic inguinal hernia repair can significantly reduce the occurrence of postoperative seroma without increasing blood loss, recovery, and hospital stay.